The effectiveness of external audit in reducing creative accounting practices (from the perspective of auditors and university professors) - Hwnar Mohammed Mohammed Amin; Soran Mohammed Amin; Mohammed Hazem Ismail Al-Ghazali (The Scientific Journal of Cihan University– Sulaimaniya, 2017)
One of the reasons of the existence of the creative accounting is the existence of difficulties and deficiency in the field of the external review. This led to the use of modern techniques and means to treat the deficiency and difficulties that face the process of review. The creative accounting process is considered a big challenge for the two careers of review and auditing through the practices, procedures and policies conducted by the accountants. The efficiency of the review helps in delimiting the creative accounting. On such basis, this paper is considered important in exploring whether the offices of reviewing take care of applying the disciplinary systems for the process of review and. It is also important in determining the level of efficiency and effectiveness before and after the application. The current study is significant as it reconsiders the process of review and the moral commitments of the accountancy as a career in addition to arousing the vocational and academic consciousness of the importance of taking much care of studying the moral commitments and achieving more understanding for what it really means. The paper aims at distinguishing the role of reviewing the audit in revealing and identifying the practices and procedures of the economic units and their accountants under what might be called the creative accounting and its monitoring (checking or supervising) procedure. The general aim of the paper is to clarify the importance of the efficiency of the effective review to delimit the practices of the creative accounting which is done through the achieving the current situation to review and identify the points of weakness and determining the obstructions which negatively influenced the reputation of the works of audits. Consequently, the exploring nature of this study which the researches relied on is the inductive method in inducing the opinions of the reviewers’ practitioners of the career and revealing the creative accounting (auditing).